Safety and Efficacy of Pure Human Cl-Esterase Inhibitor in the Treatment of Patients with Sepsis - N. B. Lazareva; A. A. Igonin (Антибиотики и Химиотерапия)
One of the new experimental trends in pharmacotherapy of sepsis is the use of C1-esterase inhibitor (C1I) from the group of immunobiological agents influencing the complement system. An open prospective study on the safety and efficacy of C1I revealed its positive effect on the death rate among the patients with sepsis. In a dose of 12000 IU, C1I had a significant inhibitory action on the complement system activity, as well as an antiinflammatory effect by blocking the complement-dependent link in the systemic inflammation. The adverse and significant adverse events were not associated with the use of C1I.